Grape seed extract alleviates radiation-induced damages in human blood lymphocytes - Reza Ghasemnezhad Targhi; Valiallah Saba (Avicenna Journal of Phytomedicine, 2020)
Objective: Ionizing radiation induces deleterious effects in the biological systems by producing free radicals. Grape Seed Extract (GSE) as a free radical scavenger could protect the body against the damages. Materials and Methods: In this study, 12 healthy male volunteers were divided into Groups 1, 2, 3 and 4 and received 100, 300, 600 and 1000 mg GSE, respectively. Peripheral blood samples were collected from each volunteer 15 min before, and 1, 2, and 5 hr after GSE oral administration. Blood samples were then irradiated with 150 cGy of 100 kvp X-ray (Irradiated control group, was treated with only 1.5 Gy of X-rays). Cytogenic damages were detected by micronucleus assay. Results: Results showed that irradiation significantly increased the incidence of micronuclei (p Conclusion: Consumption of GSE before undergoing radiation protects human lymphocytes against X-rays by reducing radiation-induced genotoxicity.